L’impropriété du dessin - Lucien Massaert (Appareil)
- Jean Clay develops a thought of the substrate (subjectile) as the non-appropriable ground that rises;- in Jacques Derrida, the taking into account of the absence or the lack of ground and foundation produces the destabilisation of the settled instances of the support and the trace in the mode of their duplication and of a gap in inscription;- for Pierre Fédida and Philippe-Alain Michaud dreams open access to a theory of the image starting from a plasticity of the dream image and an a-grammatical equivocity of the language of images. This poetics of drawing makes it possible to relate the void to spatialisation as the breath relates to speech, and makes space for the unpronounceable, for nothingness, for deprivation, for the indistinct.At the crossroads of the insurrection of the substrate (subjectile), the rise of the ground and the silence of the white, the impropriety of drawing moves forward as what eludes identification. This might be the place in the arts system, in disciplines, in the thinking of the medium that induces their opening, where the system is both undone but at the same time restored, allowing for its evolution.